An unusual case of diffuse Merkel cell carcinoma successfully treated with low dose radiotherapy. Issue 5 (14th May 2015) - Chatzinasiou, Foteini; Papadavid, Euaggelia; Korkolopoulou, Penelope; Levidou, Georgia; Panayiotides, Ioannis; Theodoropoulos, Konstadinos; Pogka, Vasiliki; Asimakopoulos, Charalampos; Rigopoulos, Dimitrios
ABSTRACT Merkel cell carcinoma (MCC) is a rare and highly aggressive neuroendocrine carcinoma of the skin. MCC should be included in the diagnosis of a rapidly growing infiltrating mass and histology as well as laboratory investigations such as Merkel cell polyoma virus (MCPyV) detection are valuable in its diagnosis. We present an unusual case of giant MCC‐positive MCPyV in a Greek woman located on the lower leg. Our patient is very unusual in terms of her extensive MCC and her rapid and complete response to radiotherapy.